Exploitation of genetic potential of sweetpotato for end-user traits improvement - Baafi, E.; Ofori, K.; Blay, E.; Gracen, V.; Manu-Aduening, J.; Carey, E.E. (African Journals Online, 2016)
Sweetpotato (Ipomoea batatas Lam) is a staple food globally, but it has remained underutilised resource in Ghana due to lack of consumer preferred cultivars. There is the need to develop staple-type sweetpotato cultivars which are preferred by consumers to increase sweetpotato use as a food security, health and industrial crop commodity in Ghana. This study was conducted to evaluate the breeding potential of sweetpotato germplasm for the development of farmer and consumer preferred varieties in Ghana. A total of 115 sweetpotato accessions were evaluated for genetic variability. Significant (P<0.01) differences were observed indicating genetic diversity. G x E was significant for all traits, except dry matter, sucrose, total sugar, and starch content. Phenotypic Coefficient of Variation (PCV) ranged from 4.78% for starch content to 63.40% for marketable root weight. Genotypic Coefficient of Variation (GCV) ranged from 4.07% for starch content to 55.35% for marketable root weight. Broad-sense heritability estimates varied from medium (0.61) to high (0.90) for all the traits, except for sucrose content. Predicted improvement over the means is 10 up to 105% for all traits, except starch (7.13%). This indicates sufficient useful genetic variation prospect which could be used to provide substantial improvement through selection of superior genotypes. The strong positive genetic association between dry matter and starch (r = 0.71), and strong negative relationship for sugar and dry matter (r = -0.77) and starch content (r = -0.99) indicates the possibility of developing non-sweet high dry matter sweetpotatoes, which are the preferred varieties in Ghana.